Social Interaction and Personal Learning Models in Islamic Education: A Humanistic and Constructivist Perspective - Muhammad Shoumil Burhanuddin Subari (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
The current practice of Islamic Religious Education (PAI) learning in schools still faces the challenge of the dominance of conventional methods that tend to be teacher-centered, so that the aspect of internalization of values by students is often not optimal . This article aims to describe the characteristics and conceptual relationships between the Social Interaction and Personal learning models in the context of PAI, while also examining the relationship between the two models with constructivist and humanistic learning theories . Through a literature study, the analysis shows that the Social Interaction model based on constructivist theory emphasizes the construction of knowledge through group dynamics, collaboration, and social interaction . Meanwhile, the Personal model based on humanistic theory is oriented towards the development of individual potential, self-awareness, and spiritual reflection . The results of the study conclude that the integration of these two models offers a holistic learning approach, where students not only understand PAI material cognitively, but are also able to actualize religious values through real social experiences and deep personal appreciation .